Penggunaan Augmented Reality Berbasis Buku Cerita Bergambar Untuk Meningkatkan Hasil Belajar IPAS Materi Siklus Air Kelas V SD N 2 Bowongso Kalikajar Wonosobo - Elis Setiawati; M. Yusuf Amin Nugroho; Aryadi Nursantoso (Publikasi Inspirasi Indonesia, 2026)
This research is driven by cognitive barriers in students' ability to visualize the abstract concept of the water cycle, which affects the optimization of learning outcomes in science for grade V of SD N 2 Bowongso. This study aims to describe student responses, analyze the implementation procedure, and test the effectiveness of Augmented Reality (AR) media based on illustrated storybooks in improving learning outcomes. Employing a quantitative approach with a Quasi-Experimental Non-equivalent Control Group design, the study involved experimental and control groups through observation and validated test instruments. The results indicate highly positive and enthusiastic student responses toward the systematic interactive learning process. Statistical analysis via t-test yielded a significance value of < 0.001, supported by an N-gain score of 0.67 (medium category) for the experimental group, which outperformed the control group's 0.47. It is concluded that integrating immersive technology into visual story narratives effectively visualizes complex natural phenomena and optimizes academic achievement. The implication of this study confirms that AR media serves as an innovative solution for elementary school teachers to optimize the teaching of abstract science materials to enhance students' scientific literacy.